Reconstruction of Tafsir Learning in Dayah Aceh - Anshari, Ismail; Rijal, Fakhrul; Amin, Maimun Abdurrahman (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
Dayah or pesantren as a traditional Islamic educational institution that has given birth to many Acehnese scholars. The existence and number of dayah in Nanggroe Aceh Darussalam is increasing. However, the fact is not balanced with innovations in learning methods, especially interpretation learning. This study aims to provide a detailed picture related to tafsir learning in Dayah Aceh. This research uses qualitative methods with a library research approach. Based on the results of the study, it was found, among others, that the learning of interpretation of most of Dayah Aceh uses the qodim (non-classical) system so that the role of students is limited. The existence of this phenomenon requires the reconstruction of interpretive learning in Dayah Aceh through the use of discovery or inquiry-discovery learning strategies; mastery of learning strategies; Unit Learning Strategies and Reception Learning Strategies